DOZ047.55: Midterm follow-up of long-gap esophageal atresia national cohort: study of feeding difficulties and morbidity. (24th June 2019) - Thomas, J; Gottrand, F; Levard, G; Lamireau, T; Michaud, L; Sfeir, R; Michel, J-L; Carcauzon, V; Pouzac, M; Branchereau, S; Petit, T; Sapin, E; et al.
Abstract: Introduction: Long-gap esophageal atresia (LGEA) leads to multifactorial morbidity. The aim of this study is to analyze midterm gastrointestinal and respiratory morbidities with special assessment of feeding difficulties. Secondary goals were to determine risk factors of malnutrition and the impact of surgical techniques on morbidity. Methods: We conducted a prospective observational national study. Using French national database, we reviewed medical charts of every patient treated for LGEA between 2008 and 2010 in France. Phone contact was proposed to assess orality disorders using Functional Oral Intake Scale (FOIS). Patients with complete data were included. We compared conservative management with esophageal replacement. Results: We included 31 cases with a median age of follow-up of 9 years [7–10]. Median z-score for weight was −0.97 [−3.52–2.50], <to −2DS in eight patients (26%). Eleven patients (35%) had a medical treatment for gastroesophageal reflux (GER), 10 children (35%) had required at least one dilatation for stricture (median number of 2 [0–10]) and 17 patients (55%) complained of food impaction. Enteral feeding was required in three patients (10%). Orality disorders were present in 16 cases (52%). Ten children (30%) required a daily treatment for asthma and 3 (10%) had recurrent pulmonary infections. Low birth weight, preterm birth, congenital malformations, GER, dysphagia, abnormal FOIS and asthma were not associated with malnutrition. Conservative strategy was significantly associated with orality disorders ( P  = 0.04). Conclusion: Midterm morbidity in LGEA concerns 80% of our population. Gastrointestinal morbidity includes mainly dysphagia, GER, and orality disorders. This study suggests that conservative management provides more orality disorders. Other studies are mandatory to confirm it.